Abdominal Adipose Tissue Associates With Adiponectin and TNFα in Middle-Aged Healthy Men - Zaidi, Hani; Aksnes, Tonje; Åkra, Sissel; Eggesbø, Heidi B.; Byrkjeland, Rune; Seljeflot, Ingebjørg; Opstad, Trine B. (Frontiers in Endocrinology, 2022)
Introduction: Adipokines are highly active biopeptides involved in glucose metabolism, insulin regulation and the development and progression of obesity and its associated diseases. It includes, among others, adiponectin, visfatin and tumor necrosis factor alpha (TNFα). The sources of adipokines and their associations with glucometabolic variables are not completely understood. Aim: In this cross-sectional study, we aimed to investigate whether gene expression levels in subcutaneous adipose tissue (SAT) of selected adipokines and their corresponding circulating levels associate with the amount of AT in superficial (sSAT), deep (dSAT) and visceral AT (VAT), assessed by computed tomography (CT). Any association with glucometabolic variables were also explored. Methods: In 103 healthy Caucasian men, fasting venous blood and SAT samples from the gluteal region were collected. Ninety-four of the participants underwent CT assessment of the abdominal AT, which was divided into VAT, sSAT and dSAT. Circulating levels of adipokines were measured by ELISA and AT gene-expression by PCR. Insulin sensitivity was determined by glucose clamp, assessing glucose disposal rate (GDR). Results: Circulating adiponectin and TNFα gene expression correlated inversely and positively to the amount of AT in all three compartments (r=-0.266 to -0.276, p<0.05 for all) and (r=0.323 ¬- 0.368, p<0.05 for all), respectively, with strongest correlations to the amount in sSAT and dSAT. When dividing AT compartments into quartiles, a tendency was observed towards lower circulating adiponectin and higher TNFα gene expression levels, respectively, with increasing amount of sSAT and dSAT. Circulating adiponectin correlated inversely to insulin, C-peptide and waist circumference (r=-456 to -0.373, p<0.001) and positively to GDR (r=0.356, p<0.001). AT-expressed visfatin correlated inversely to insulin and C-peptide (r=-0.370 and r=-0.404, p<0.001). Conclusion: Increased amount of AT is associated with lower levels of adiponectin and increased levels of TNFα AT expression.